G346(P) Driving up standards and minimising risk: relieving the burden of jaundice management in the emergency department (ed). (12th March 2018) - Scanlon, N; Anpananthar, A; Mistry, R
Abstract : Background and aims: Jaundice represents a significant burden on ED workload. Long waiting times for assessment and investigation can lead to delays in treatment and discharge. Method: The team used audit and DATIX reports to assess care of babies presenting to ED with jaundice. Quality improvement initiatives were implemented based upon results, and a reaudit assessed their impact. Results: A total of 272 cases presenting in the year 2016 were analysed. Areas for improvement were found to be; time to serum bilirubin result (mean 168 min, range 28–508 min) and time spent in department (mean 245 min, range 37–716). Causes of delay included prolonged waits for medical assessment and laboratory delays in sample analysis. The DATIX system identified key cases where patient care was deemed to fall short of expected standards. Serious incident (SI) reporting identified cases where harm may have arisen. Conclusion and recommendations: Using our data and incorporating DATIX and SI reporting, we secured financial and managerial investment to implement our recommendations. Our primary intervention was the creation of an in-hours nurse-led jaundice clinic. This alternative pathway is intended to relieve burden in ED and facilitate access to faster assessment and treatmen. For patients presenting out of hours, we improved point of care testing by obtaining a transcutaneous bilirubinometer and recalibrating the blood gas analyser to improve accuracy thus removing the need for processing lab serum samples. Education targeted at triage nurses in ED has enabled them to initiate basic investigations and management whilst awaiting medical assessment. Going forward, we have also been able to secure an application for a Biliblanket which will aid the timely administration of phototherapy in ED. A re-audit of three months of data following implementation of these initiatives has shown a 56% reduction in mean waiting time for bilirubin results and 49% reduction in mean time spent in ED. This project highlighted the benefit of a multifaceted approach to quality improvement, incorporating multiple pillars of clinical governance to advance patient care.